2013
DOI: 10.1371/journal.pone.0082373
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Nasal Polyp Disease Involves Early Nasal Mucosal Inflammation and Remodelling

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by both a chronic inflammation and tissue remodelling; as indicated by extracellular matrix protein deposition, basement membrane thickening, goblet cell hyperplasia and subepithelial edema, with reduced vessels and glands. Although remodelling is generally considered to be consequence of persistent inflammation, the chronological order and relationship between inflammation and remodelling in polyp development is still not clear. The aim of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 54 publications
6
130
1
8
Order By: Relevance
“…Also, subjects were allocated to a phenotype during office endoscopy before surgery, and the clinical differentiation might be unclear in some cases were polyps were only observed during surgery. In cases of middle turbinate-confined polypoid oedema, the phenotype might not be clear-cut during office endoscopy, and it has been shown that early stage nasal polyps already show eosinophilic inflammation 15,23 . The production of Th17-family derived cytokines IL-17A and IL-22 correlated modestly as was shown by the principal components analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, subjects were allocated to a phenotype during office endoscopy before surgery, and the clinical differentiation might be unclear in some cases were polyps were only observed during surgery. In cases of middle turbinate-confined polypoid oedema, the phenotype might not be clear-cut during office endoscopy, and it has been shown that early stage nasal polyps already show eosinophilic inflammation 15,23 . The production of Th17-family derived cytokines IL-17A and IL-22 correlated modestly as was shown by the principal components analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In CRSwNP, epithelial cell disruption is extensive in whole nasal tissue samples 88 and excess mucus can be explained by goblet cell hyperplasia and mucin hypersecretion. 89 BM thickening relates to disease severity and duration, along with the presence of underlying asthma 90 and seems to be independent of the degree of eosinophilic inflammation.…”
Section: Ch Ronic R Hin Osin Usitis and Sinon Asal Remodellingmentioning
confidence: 99%
“…Reductions of the tight junction proteins claudin-1 and occludin in CRS tissues were reported in another study 50 . The group of Bachert reported that ZO-1, occludin and E-cadherin were all reduced in mature polyps removed from CRSwNP patients 51 . Moreover, aquaporin 5, a marker of epithelial differentiation, was significantly reduced in sinonasal samples of CRSwNP subjects compared to CRSsNP or controls 52 .…”
Section: Barrier Defects In Type 2 Diseasesmentioning
confidence: 99%
“…More recent studies found similar evidence for increased EMT in allergic rhinitis 42, 43 . Several studies have demonstrated ongoing EMT in CRS 37, 47, 4951 . Two studies have demonstrated ongoing EMT in eosinophilic esophagitis 62, 124 .…”
Section: Mechanisms Of Barrier Defectsmentioning
confidence: 99%